DESIGN OF UNDERWATER REMOTE OPERATED VEHICLE (UW-ROV) WITH CAMERA, TEMPERATURE AND DEPTH SENSOR IN OPTIMUM COST - Komal Achugatla1, Shraddha Gajakosh2, Deepjyoti Sathe3, Rutuja Tarapurkar4; Dr. R. R. Gidde; Ameet Rupnar (International Journal of Innovations in Engineering Research and Technology, 2022)
Remotely operated underwater vehicles (ROVs) are remote control underwater robots driven by an individual on the surface.Generally,ROVs are equipped with a video camera, propulsion system, and lights.Other equipment is added depending on the specifications required. Water temperature influences the rates of chemical and biological processes and affects other measured parameters. Now a days, depth information is critical for safe treatment of the water to ensure environmental safety and protect the health of the pond environment for the animals living there. So, that is required to develop ROV with temperature and depth sensors through which we can measure temperature, and depth. There are various ROVs with temperature and depth sensors available in market. But as they are costly or may be with needless additional features. It is required to develop an underwater ROV with temperature and depth sensor in optimum cost. The ROV was constructed by low-cost material like commercial grade polyvinyl chloride (PVC) pipes. This ROV is equipped with Micro IP ROV Camera and ISD4000 Depth and Temperature sensor. This ROV is able to submerge up to 20meters into water to perform underwater observation operation.